Refleksi Kisah Isra Mi’raj dalam Pendidikan dan Masyarakat di Masjid As-Shobirin Teluk Pandan - Rani, Nur Maha; Hidayat, Muhammad Rachmad; Elpina, Elpina; Faelasup, Faelasup (MAYARA: Jurnal Pengabdian Masyarakat, 2025)
STAI Sangatta students carry out the Community Service Program (PkM) through social service activities with the aim of increasing knowledge and insight in the fields of education and society. One of the challenges faced by the community is the lack of interest among teenagers in the area to be active in religious activities, especially at the As-Shobirin Mosque, Teluk Pandan Village. Lack of participation in Islamic activities, including congregational prayers, is a major problem. To overcome this, the PkM team is trying to revive interest and a positive image of the mosque through activities to commemorate Isra Mi'raj. The method applied in Community Service includes planning, implementation, as well as monitoring and evaluation stages. Through this social service activity, students as organizers get positive benefits and the surrounding community also feels the positive impact and friendship is established between all parties involved.